Effectiveness of a perioperative pulmonary rehabilitation program following coronary artery bypass graft surgery in patients with and without COPD - Chen, Jui-O (Int J Chron Obstruct Pulmon Dis, 2018)
PURPOSE: It is unclear whether the effectiveness of pulmonary rehabilitation program (PRP) after cardiac surgery differs between patients with and without COPD. This study aimed to compare the effectiveness of PRP between patients with and without COPD undergoing coronary artery bypass graft (CABG) surgery. PATIENTS AND METHODS: We retrospectively included patients who underwent CABG surgery and received 3-week PRP from January 2009 to December 2013. We excluded patients who underwent emergency surgery, had an unstable hemodynamic status, were ventilator dependent or did not complete the PRP. Demographics, muscle strength, degree of dyspnea, pulmonary function and postoperative complications were compared. RESULTS: Seventy-eight patients were enrolled (COPD group, n=40; non-COPD group, n=38). Maximal inspiratory pressure (MIP; −34.52 cmH(2)O vs −43.25 cmH(2)O, P<0.01; −34.67 cmH(2)O vs −48.18 cmH(2)O, P<0.01), maximal expiratory pressure (MEP; 32.15 cmH(2)O vs 46.05 cmH(2)O, P<0.01; 37.78 cmH(2)O vs 45.72 cmH(2)O, P<0.01) and respiratory rate (RR; 20.65 breath/minute vs 17.02 breath/minute, P<0.01; 20.65 breath/minute vs 17.34 breath/minute, P<0.01) in COPD and non-COPD groups, respectively, showed significant improvement, but were not significantly different between the two groups. Forced vital capacity (FVC; 0.85 L vs 1.25 L, P<0.01), forced expiratory volume in 1 second (FEV(1); 0.75 L vs 1.08 L, P<0.01), peak expiratory flow (PEF; 0.99 L vs 1.79 L, P<0.01) and forced expiratory flow between 25% and 75% of vital capacity (FEF(25–75); 0.68 L vs 1.15 L, P<0.01) showed significant improvement between postoperative Days 1 and 14 in the COPD group. FVC (1.11 L vs 1.36 L, P<0.05), FEV(1) (96 L vs 1.09 L, P<0.05) and FEF(25–75) (1.03 L vs 1.26 L, P<0.05) were significantly improved in the non-COPD group. However, only PEF (80.8% vs 10.1%, P<0.01) and FEF(25–75) (67.6% vs 22.3%, P<0.05) were more significantly improved in the COPD group than in the non-COPD group. CONCLUSION: PRP significantly improved respiratory muscle strength and lung function in patients with and without COPD who underwent CABG surgery. However, PRP is more effective in improving PEF and FEF(25–75) in COPD patients.